Improving Intergroup Relations Through Online Contact - Amzalag, Meital; Shapira, Noa (International Review of Research in Open and Distributed Learning, 2021)
This study examined an online professional development program designed to support meaningful acquaintance and reduce stereotypes and prejudices among teachers from different cultures in Israeli society. The rationale of the online program was based on the premise that indirect online contact might improve intergroup relations in diverse societies. The program was designed to progress gradually, starting from basic and leading to a deeper acquaintance, using a variety of computer-mediated communication (CMC) tools. Findings indicated that upon program completion, participants were more respectful towards one another than pre-program. They held a positive view of online learning and were open to multiculturalism (more tolerant and accepting of others than previously) while still maintaining their respective cultural identities. The program participants noticed the gradual progression in task design, expressly noting that this stepwise structure supported forging a connection and then fostering familiarization. This study fills a gap in the research through demonstrating ways that online contact (indirect contact) can be used to promote acquaintance and reduce stereotypes and prejudices among teachers from different groups in Israeli society.